Mean Years of Schooling Inequality and Return on Education: Analysing the Main Determining Factors - Riyadi, Deden Rizal; Hendajany, Nenny; Kamaruddin, Roslina (UUM Press, 2023)
Education is a determining factor in human development. West Java had a mean year of schooling (MYS) of around 8.37 years in 2019, which is still below the compulsory primary school. This study aims to find out the factors that can be attributed to low MYS. Ten variables influence the MYS. Principal Component Analysis (PCA) method was used to simplify the observed variables by reducing the dimensions. The result reduces ten variables to two factors containing five variables. The first factor is infrastructure (road access, distance to schools, and health centres) and the second factor is income (RMW and GRDP). These two factors significantly influence the MYS. This MYS, in turn, directly affects people’s food consumption. A higher percentage of income for non-food represents a higher return to education. Districts have a lower return on education than cities. Two factors (infrastructure and income) do not directly affect the percentage of people’s income for food but are affected through MYS. The central and provincial governments need to pay more attention to districts with an agricultural base on the availability of school infrastructure. In addition, it is necessary to increase people’s income by providing better road access to reach better education.